2022
DOI: 10.1002/macp.202200052
|View full text |Cite
|
Sign up to set email alerts
|

The Birth of Fluorescence from Thermally Polymerized Glycine

Abstract: Thermal polymerization of glycine, the simplest amino acid bearing only one alfa carbon atom, is not an efficient process in mild conditions. Hydrothermal processing of glycine produces only small peptides, up to four units on average, with only a fraction of glycine that reacts. In the present work, boric acid is used as a catalyst to promote the formation of glycine polypeptides. The final product is characterized by an extended polymeric structure and an intense blue fluorescence characterizes the final pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…0.128 g of l -lysine were solubilized in 10 mL of distilled H 2 O (0.87 M). The solutions were placed into a Teflon-lined stainless steel autoclave 7 with a capacity of 50 mL and then heated at 130 or 200 °C for 15 h. After the hydrothermal treatment (HT), the obtained products were cooled down to 20 °C and then used for the characterizations. The samples hydrothermally treated at 130 and 200 °C are indicated in the text as HT-130 °C and HT-200 °C.…”
Section: Methodsmentioning
confidence: 99%
“…0.128 g of l -lysine were solubilized in 10 mL of distilled H 2 O (0.87 M). The solutions were placed into a Teflon-lined stainless steel autoclave 7 with a capacity of 50 mL and then heated at 130 or 200 °C for 15 h. After the hydrothermal treatment (HT), the obtained products were cooled down to 20 °C and then used for the characterizations. The samples hydrothermally treated at 130 and 200 °C are indicated in the text as HT-130 °C and HT-200 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has experimentally demonstrated that polymers with strong emission in the blue region can be obtained from nonaromatic amino acids such as l -lysine and glycine …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Our research group has experimentally demonstrated that polymers with strong emission in the blue region can be obtained from nonaromatic amino acids such as L-lysine 2 and glycine. 9 L-lysine, in particular, forms branched and hyperbranched structures via thermal polymerization. These polymers are chromophores and exhibit well-defined lifetime, quantum yield, and correlated absorption−emission spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This interest is partly due to glycine's simple structure, high solubility in water, and its role as a building block for proteins, making it an ideal candidate for synthesizing complex materials through thermal treatment or polymerization processes. Its simplicity (composed merely of a backbone connected to a single hydrogen atom) facilitates easier manipulation and predictable outcomes during synthesis procedures, allowing for the formation of linear peptides through thermal polymerization, even under conditions that are not typically favorable for such reactions [22]. Moreover, during heat treatment, glycine displays distinctive characteristics, such as being able to participate in decarbonylation and cyclodehydration reactions, ultimately contributing to the generation of heterocycles relevant to CN x materials.…”
Section: Introductionmentioning
confidence: 99%